2005
DOI: 10.1007/s11910-005-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

New autosomal recessive cerebellar ataxias with oculomotor apraxia

Abstract: Autosomal recessive cerebellar ataxias (ARCAs) are a phenotypically and genetically heterogeneous group of diseases. Recently, a subgroup of ARCA associated with oculomotor apraxia (AOA) has been delineated. It includes at least four distinct genetic entities: ataxia-telangiectasia, ataxia-telangiectasia-like disorder, and ataxia with oculomotor apraxia type 1 (AOA1) and type 2 (AOA2). The phenotypes share several similarities, and the responsible genes, ATM, MRE11, APTX, and SETX, respectively, are all implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…A distinct form of AOA linked to chromosome 9q34, AOA2 also has an overlapping clinical phenotype with the three disorders described in the previous paragraph (Nemeth et al, 2000; Duquette et al, 2005; Le Ber et al, 2005). This syndrome is characterized by cerebellar atrophy, oculomotor apraxia, peripheral neuropathy, and elevated serum α-fetoprotein in some cases (Le Ber et al, 2005; Criscuolo et al, 2006).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…A distinct form of AOA linked to chromosome 9q34, AOA2 also has an overlapping clinical phenotype with the three disorders described in the previous paragraph (Nemeth et al, 2000; Duquette et al, 2005; Le Ber et al, 2005). This syndrome is characterized by cerebellar atrophy, oculomotor apraxia, peripheral neuropathy, and elevated serum α-fetoprotein in some cases (Le Ber et al, 2005; Criscuolo et al, 2006).…”
Section: Introductionmentioning
confidence: 72%
“…This syndrome is characterized by cerebellar atrophy, oculomotor apraxia, peripheral neuropathy, and elevated serum α-fetoprotein in some cases (Le Ber et al, 2005; Criscuolo et al, 2006). The gene defective in AOA2, SETX , was recently identified (Moreira et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that A-T is the second most common cause of ataxia [11,53,54]. However, in the three studies that tested for both AOA and A-T genes, AOA was found to be more common in two studies (in Portugal and Alsace), while A-T was more common in Norway.…”
Section: Discussionmentioning
confidence: 97%
“…Senataxin is thought to be involved in double strand break DNA repair and response to oxidative stress but also in transcription regulation via exon splicing (Airoldi et al 2009, Suraweera et al 2007, Suraweera et al 2009). Patients with AOA2 have elevated α-fetoprotein (AFP) levels, a tumor marker (Anheim et al 2009b, Le Ber et al 2005), but without increased occurrence of cancer as observed in ataxiatelangiectesia. Oculomotor apraxia is not a systematic finding and appears to be present in about 50% of patients (Anheim et al 2009b).…”
Section: Introductionmentioning
confidence: 99%